2017
DOI: 10.1371/journal.pone.0179894
|View full text |Cite
|
Sign up to set email alerts
|

Right wing authoritarianism is associated with race bias in face detection

Abstract: Racial discrimination can be observed in a wide range of psychological processes, including even the earliest phases of face detection. It remains unclear, however, whether racially-biased low-level face processing is influenced by ideologies, such as right wing authoritarianism or social dominance orientation. In the current study, we hypothesized that socio-political ideologies such as these can substantially predict perceptive racial bias during early perception. To test this hypothesis, 67 participants det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
1
3
0
1
Order By: Relevance
“…We found that RWA was negatively related specifically to the automatic processing of power cues, but not to automatic processing of an arbitrary concept such as gender. This result fits previous research that found RWA to go along with race bias in early face perception, such that higher RWA slowed responses when detecting out‐group faces (Bret et al, 2017). This example shows associations of RWA with another phenomenon related to the content of the construct.…”
Section: Methodssupporting
confidence: 91%
“…We found that RWA was negatively related specifically to the automatic processing of power cues, but not to automatic processing of an arbitrary concept such as gender. This result fits previous research that found RWA to go along with race bias in early face perception, such that higher RWA slowed responses when detecting out‐group faces (Bret et al, 2017). This example shows associations of RWA with another phenomenon related to the content of the construct.…”
Section: Methodssupporting
confidence: 91%
“…No que diz respeito à validação discriminativa, os resultados apontam uma correlação positiva entre a ERR e a escala de autoritarismo (RWA). Esse resultado era esperado, uma vez que sabemos que o autoritarismo é uma das bases do racismo (Bret, Beffara, McFadyen, & Mermillod, 2017…”
Section: Resultsunclassified
“…In the literature, stronger Right Wing Authoritarianism scores have reportedly been related to slower response times for detecting out-group rather than ingroup faces. It is therefore hypothesized that socio-political ideologies, such as Right Wing Authoritarianism might foster early racial bias through attentional disengagement towards out-group faces [92]. If so, for individuals reporting stronger Right Wing Authoritarianism ideologies, the correlated enhanced caudate activity might support selective attention to the valuable and rewarding in-group faces.…”
Section: Discussionmentioning
confidence: 99%